The Fekete Szegö problem for a subclass of quasi-convex functions with respect to symmetric points - Aini Janteng; Chuah, Puoi Choo (Universiti Tunku Abdul Rahman, 2014)
The purpose of the present paper is to introduce the class KS∗(α, β ), subclass of quasi-convex functions with respect to (w.r.t) symmetric points. Sharp upper bounds for an , an , n = 2, 3, 4 and the Fekete-Szegö inequalities are considered for functions belonging to the class KS∗(α, β ).